2022
DOI: 10.3389/fcimb.2022.759156
|View full text |Cite
|
Sign up to set email alerts
|

Network-Based Differences in the Vaginal and Bladder Microbial Communities Between Women With and Without Urgency Urinary Incontinence

Abstract: BackgroundLittle is known about the relationship of proximal urogenital microbiomes in the bladder and the vagina and how this contributes to bladder health. In this study, we use a microbial ecology and network framework to understand the dynamics of interactions/co-occurrences of bacteria in the bladder and vagina in women with and without urgency urinary incontinence (UUI).MethodsWe collected vaginal swabs and catheterized urine specimens from 20 women with UUI (cases) and 30 women without UUI (controls). W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 84 publications
0
12
0
Order By: Relevance
“…Several studies have noted that a variety of vaginal microbial variations and the key bacteria concentrations are related to a higher risk of contracting HIV through several different potential pathways, including the yield of HIVinducing factors, inflammation [87], or by disrupting chemical and physical barriers to HIV [88]. Additionally, other vaginal infections including BV, which is marked by the presence of complicated anaerobic bacteria in the vagina, support HIV transmission [89]. Young South African women with very diversified vaginal microbial communities had an abundance of genital CD 4-positive T-cells that were activated, and as a result of recent investigation, they had four times the risk of contracting HIV than women with less diverse and L. crispatusdominant vaginal microbiomes [90].…”
Section: Risk Of Hiv and The Vaginal Microbiotamentioning
confidence: 99%
“…Several studies have noted that a variety of vaginal microbial variations and the key bacteria concentrations are related to a higher risk of contracting HIV through several different potential pathways, including the yield of HIVinducing factors, inflammation [87], or by disrupting chemical and physical barriers to HIV [88]. Additionally, other vaginal infections including BV, which is marked by the presence of complicated anaerobic bacteria in the vagina, support HIV transmission [89]. Young South African women with very diversified vaginal microbial communities had an abundance of genital CD 4-positive T-cells that were activated, and as a result of recent investigation, they had four times the risk of contracting HIV than women with less diverse and L. crispatusdominant vaginal microbiomes [90].…”
Section: Risk Of Hiv and The Vaginal Microbiotamentioning
confidence: 99%
“…Pearce et al found an increase in Gardnerella and a decrease in Lactobacillus in urinary microbiome were associated with female urgent urinary incontinence [ 73 ]. By using network analysis to study the microbiota between the vagina and bladder, Nardos et al pointed out a loss of diversity in urinary microbiota, which means the bladder bacterial genera are more likely to overlap with vagina bacterial genera, and this could be associated with female urgent urinary incontinence (43% in incontinent women vs. 29% in controls) [ 74 ].…”
Section: The Role Of Dysbiosis Between Mets and Oab Syndrome In Persp...mentioning
confidence: 99%
“…Gut or urinary dysbiosis is one of the overlapping mechanisms between metabolic syndrome and overactive bladder. Gut flora can migrate to the urinary bladder via vagina colonization in women [ 74 ]. ( B ).…”
Section: Figurementioning
confidence: 99%
“…Previously, we published an analysis of 149 genomes of 78 different species isolated from the female bladder [14]. Several of the taxa found within the bladder microbiota are also inhabitants of the vaginal microbiota [14,21,22]. This led us to posit that the bacterial communities of these two anatomical sites may be connected [14].…”
Section: Introductionmentioning
confidence: 99%
“…This led us to posit that the bacterial communities of these two anatomical sites may be connected [14]. A recent 16S rRNA gene sequencing survey of paired bladder and vaginal samples identified more bacterial genera within the bladder than within the vagina, suggesting a greater bacterial diversity within the urinary tract [22]. In contrast, little overlap in species was reported between the microbiota of the urinary and gastrointestinal tracts [14], despite prior evidence that the gastrointestinal tract is the source of E. coli that cause urinary tract infections (UTIs) [23][24][25][26].…”
Section: Introductionmentioning
confidence: 99%